Extraction, structure analysis and antioxidant activity of Sibiraea laevigata (L.) Maxim polysaccharide - Xuhua Yang; Jutian Yang; Honghai Liu; Zhongren Ma; Penghui Guo; Hong Chen; Dandan Gao (International Journal of Food Properties, 2022)
Sibiraea laevigata (L.) Maxim (SLM) is a kind of traditional Tibetan food homologous plant with health-protection function. In this paper, PEG-UAEE method was used to extract SLMPs. The effects of different experimental parameters on the extraction efficiency of SLMPs were optimized by RSM. The results showed that the optimal extraction conditions were as follows: PEG-400 concentration of 30%, E/S ratio of 21 U/g, ultrasonic time of 2 h, extract pH value of 4.0, ultrasonic power was kept at 400 W, and ultrasonic temperature of 80°C. The SLMPs yield and content could reach at 10.95% and 21.82%, respectively. Then, the preliminarily structure of SLMPs was characterized by HPLC, FT-IR, and SEM. It was found that the SLMPs were typical hetero polysaccharides considering the main constitutive monosaccharides including galactose (13.34%), glucose (46.76%), rhamnose (8.78%), fructose (2.89%), and arabinose (11.79%). The FT-IR analysis indicated that SLMPs are pyran-type polysaccharides containing α-glycosidic bonds, β-glycosidic bonds, and the SEM analysis showed that SLMPs have a prominent non-crystal structure. Moreover, SLMPs exhibited significant antioxidant activities, the IC50 values of the SLMPs for DPPH, hydroxyl, and superoxide radicals scavenging activities were 0.42, 2.08, and 0.28 mg/mL, respectively. The results suggest that SLMPs have potential applications as natural antioxidants and food ingredients in functional foods.